New modules and assembled systems for the controlled release of drugs in combination / Camillo Benetti - Camillo, Benetti (Institute of Graduate Studies, UiTM, 2016)
Dome Matrix technology is a platform for the controlled release of drug. This technology is based on the assembling of modules used as elements for controlling the drug release. The research project of the doctorate thesis was devoted to the application of Dome Matrix technology for the preparation of gastro-retentive dosage forms thanks to the module assembly in void configuration. According to the co-tutorship agreement, the research was carried out both at University of Parma and University Teknologi MARA, Kuala Lumpur. During the first part of the project, carried out at University of Parma, a modular assembled system for a double pulse release (immediate and delayed release) of esomeprazole in combination with sucralfate was studied. The assembled system was build up by assembling 5 modules, three sucralfate modules and two esomeprazole modules, in “mixed” configuration (void and stacked configurations) with three different release kinetics. The alkalizing agent in the esomeprazole immediate release module prevented the degradation of the drug in acid environment in vitro…